2008
DOI: 10.2337/dc08-0825
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Triglyceride Levels Over Time and Risk of Type 2 Diabetes in Young Men

Abstract: OBJECTIVE -The association between changes in triglyceride concentrations over time and diabetes is unknown. We assessed whether two triglyceride determinations obtained 5 years apart can predict incident type 2 diabetes.RESEARCH DESIGN AND METHODS -Triglyceride levels at baseline (time 1) and 5 years later (time 2), followed by subsequent follow-up of 5.5 years, were measured in 13,953 apparently healthy men (age 26 -45 years) with triglycerides Ͻ300 mg/dl (Ͻ3.39 mmol/l).RESULTS -During 76,742 person-years, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
137
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(150 citation statements)
references
References 27 publications
13
137
0
Order By: Relevance
“…Moreover, several cohort studies of older individuals have proposed that the TG level is an independent risk factor for diabetes [27,28]. A recent report demonstrated that TG levels of >120 mg/ dL, which is lower than that included in the criteria for metabolic syndrome (i.e., >150 mg/dL), were associated with greater diabetes risk compared with levels of < 66 mg/dL in young healthy males [29]. These findings also support our results.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, several cohort studies of older individuals have proposed that the TG level is an independent risk factor for diabetes [27,28]. A recent report demonstrated that TG levels of >120 mg/ dL, which is lower than that included in the criteria for metabolic syndrome (i.e., >150 mg/dL), were associated with greater diabetes risk compared with levels of < 66 mg/dL in young healthy males [29]. These findings also support our results.…”
Section: Discussionsupporting
confidence: 91%
“…HDL was a risk factor of development of non -insulin dependent diabetes in middle aged British men [11,12]. A study was done by Amir Tirosh et al [13] and demonstrated that the changes in triglyceride levels in over a time and it became a risk factor for diabetes in healthy young men [12,13]. Similar results were found in our present study that Triglyceride level is a risk factor for the progression or development of Type 2 DM in an individual.…”
Section: IVsupporting
confidence: 87%
“…Another potential explanation for the apparently conflicting reports in the literature may arise from lack of careful adjustment to the various risk factors (such as fasting glucose, HDL-cholesterol, triglycerides, and blood pressure) as continuous variables within risk factor groups. This is especially important in young adults, in whom diabetes risk attributed to increased levels of FPG, triglycerides, or WBCs could be demonstrated already within what is currently considered to be the normal range for these parameters (9,12,18). The definition of MH used in our study, along with an additional adjustment for other known risk factors (Fig.…”
Section: Discussionmentioning
confidence: 94%